Comprehensive management of recurrent thyroid cancer: An American Head and Neck Society consensus statement: AHNS consensus statement. Issue 12 (22nd September 2016) - Scharpf, Joseph; Tuttle, Michael; Wong, Richard; Ridge, Drew; Smith, Russell; Hartl, Dana; Levine, Robert; Randolph, Gregory
Abstract: This American Head and Neck Society (AHNS) consensus statement focuses on the detection and management of recurrent thyroid cancer. This document describes the radiologic approach to defining structural recurrent disease and the operative and nonoperative rationale in addressing identified structural disease to create equipoise in the personalized treatment strategy for the patient. The recommendations of this AHNS multidisciplinary consensus panel of the American Head and Neck Society are intended to help guide all multidisciplinary clinicians who diagnose or manage adult patients with thyroid cancer. The consensus panel is comprised of members of the American Head and Neck Society and its Endocrine Surgical Committee, and there is representation from medical endocrinology and both national and international surgical representation drawn from general/endocrine surgery and otolaryngology/head and neck surgery. Authors provided expertise for their respective sections, and consensus recommendations were made regarding the evaluation and treatment of recurrent thyroid cancer. Evidence‐based literature support is drawn from thyroid cancer studies, recurrent thyroid cancer studies, and American Thyroid Association (ATA) guidelines. The manuscript was then distributed to members of the American Head and Neck Society Endocrine Committee and governing counsel for further feedback. © 2016 Wiley Periodicals, Inc. Head Neck 38: 1862–1869, 2016